Trabajo en alturas en el sector de la construcción en las zonas francas de Mosquera y sopo Cundinamarca (2015)
One of the main causes of accidents and death of workers in Colombia is given in working at heights, so it is classified as a high risk activity. The country has committed public bodies exercising the functions of consulting, training, evaluation, monitoring, safety inspection and control in the construction sector. These entities are: the Ministry of Labour, the Ministry of Health and Social Protection, the Service national Learning SENA, national Health, ARL positive, in partnership with private entities as managers of occupational hazards, also collaborate in the development, publication and dissemination of technical guidelines that guide standardized working conditions and control of unsafe acts, aimed at reducing risks work at heights and ensure the welfare of staff exposed;; with the aim of involving employers and workers in compliance with the regulations, implementation of safety and industrial hygiene and the use of personal protection, achieving thereby prevent accidents at work